Pengaruh Celebrity Endorser dan Sikap Pada Iklan Terhadap Sikap Pada Merek dan Loyalitas (Studi Empiris Pengguna Kartu Prabayar IM3 di Surakarta - Aji, Lintang Pamugar Mukti (STIE Surakarta, 2015)
The purpose of this research was to analyze the effect of celebrity endorser and attitude toward advertising on attitude toward brand and consumer loyalty.This research used design explanatory. Population were IM3 prepaid card consumers in Surakarta. The sampling techniquewas convenience sampling with 100 respondents. Analysis used validity test, reliability test, t-test, f-test, R Square test and path analysis. The results showed that celebrity endorser significant affected on attitude toward brand. Attitude toward advertising significant affected on attitude toward brand. Celebrity endorser significant affected on consumer loyalty. Attitude toward advertising significant affected on consumer loyalty. Attitude toward brand significant affected on consumer loyalty. Celebrity endorser and attitude toward advertising affected on attitude toward brand simultaneous. Celebrity endorser, attitude toward advertising and attitude toward brand affected on consumer loyalty simultaneous. The coefficient of determination of total results (R2) was 59,0% so consumer loyalty can be explained variable celebrity endorser, attitude toward brand within attitude toward brand as a intervening variables and the remaining 41.0% was explained variables outside the model. Celebrity endorser is a proven direct and indirect effect on consumer loyalty. Directly affect celebrity endorser on consumer loyalty has regression coefficient is greater than regression coeficient the effect of celebrity endorser on consumer loyalty through attitude toward brand. Attitude toward advertising is a proven direct and indirect effect on consumer loyalty. Directly affect attitude toward advertising on consumer loyalty has regression coefficient is greater than regression coeficient regression the effect of attitude toward advertising on consumer loyalty through attitude toward brand. Based on the result above the variable of attitude toward brand is less effective as intervening variable.